A priority list of environmental health issues for Malaysia - Hashim, Jamal Hisham; Hashim, Zailina; Hod, Rozita; Jalaludin, Juliana; Mohamed, Norlen; Karuppannan, Subramaniam; Mazeli, Ahmad Riadz; Sahrani, Suhaily; Zulkaflli, Zairul Ain (De Gruyter, 2022)
Objectives: Environmental risk factors contribute to 24% of the global burden of disease from all causes in disability-adjusted life years (DALYs), and to 23% of all global deaths. Malaysia being an advanced developing country, there is a need to prioritise environmental health issues to enable environmental health practitioners to focus on the most significant and urgent environmental health concerns. Content: This project was undertaken by a Thematic Working Group on Environmental Health Experts (TWG 10) under the Malaysian National Environmental Health Action Plan. Sixteen pre-selected environmental health issues were presented to a two focus group discussions among 20 environmental health and related professionals who then scored each issue on its magnitude and severity scale. Summary: The total of these scores generated a list of priority environmental health issues for Malaysia. Children environmental health came out as the environmental health issue of the highest priority. Outlook: We hope that this list of priority environmental health issues will be used for prioritising academic and professional manpower training, research funding allocation and planning for intervention programmes by various stakeholders.